Ethnic politics in Chinese education and role of Malaysian NGOs in Malaysia-China educational exchange, 1974-2015 - Nan, Xia (2018)
Malaysia and China have established diplomatic relations for more than 40 years. The bilateral relations between China and Malaysia are mainly based on the economic and trade fields, followed by tourism, and then is the field of education. As one of the most important aspects of Malaysia-China relations, the development in educational area is lagging behind. Educational exchange between Malaysia and China has an important interaction with Chinese education in Malaysia and political relations between Malaysia and China. Chinese education in Malaysia is twisted with Malaysian ethnic politics and its development is undoubtedly a hotly contested area. Malaysian NGOs play an important role in the process of promoting educational exchange. Nowadays, “the Belt and Road” brings the chance for the cooperation of educational exchange between Malaysia and China. Based on the above problem, the objectives of this thesis are to elaborate the background and achievement of educational exchange between Malaysia and China since they established formally diplomatic relations in 1974, to examine the relations between ethnic politics and Chinese education in Malaysia and to determine the roles of Malaysian NGOs towards educational exchange between Malaysia and China. The research is an exploratory qualitative research. The primary data were collected through semi-structured interviews and secondary data included official reports, Memorandum of Understanding (MOUs), journal articles, newspapers, website pages and online resources. The informants are 24 persons who were selected based on the purposive sampling method and snowball strategy, which were divided into three categories: politicians, social activists and scholars. For data analysis, the study applied qualitative content analysis. In addition, structuration theory was used in this study. The results show, educational exchange between Malaysia and China has a positive correlation with Malaysia-China relations, i.e. good bilateral relations of Malaysia and China can promote educational exchange, and vice versa. Meantime,Chinese education in Malaysia was greatly influenced by Malaysian ethnic politics. Therefore, it can be seen that Malaysian ethnic politics indirectly affect educational exchange between the two countries. In this process, there are three main important NGOs that play a significant role in promoting educational exchange between Malaysia and China, which are Dong Jiao Zong, the Association of Graduates from Universities and Colleges in China, Malaysia (AGUCCM) and Malaysia-China Friendship Association (MCFA). Nowadays, with the rise of China and the promotion of “the Belt and Road”, Malaysia-China relations enter the most splendid period in history, Meanwhile, under such background, educational exchange between Malaysia and China will become progressive. It can be expected that educational exchanges and Malaysia-China relations will enter a more perfect and better stage which benefits people of the two countries.